1984
DOI: 10.1111/j.1600-0609.1984.tb00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatibility antigen frequencies in patients with chronic lymphocytic leukaemia: Possible identification of a subgroup with relatively benign disease

Abstract: A series of 57 patients with chronic lymphocytic leukaemia was typed for HLA-A, B and DR antigens and compared with a control population of equal size. There was an increased frequency of HLA-A1 and B8 in the patient group, although it was not statistically significant after allowance for the number of specificities tested. A subgroup of patients lacking both A1 and B8 differed from the others in sex ratio, degree of lymphocytosis and incidence of hypogammaglobulinaemia at presentation. This subgroup also had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
(1 reference statement)
1
6
0
Order By: Relevance
“…A similar finding was also reported by others [20], though controversial results have also been published [16,21,22,25,33]. An increased frequency of the HLA-B35 allele has also been reported in some other malignancies and autoimmune diseases from different ethnic populations, including Hodgkin's lymphoma [34], autoimmune thyroiditis [35], autoimmune hepatitis [36] autoimmune arthritis [37], Moyamoya [38], and pemphigus vulgaris [39], suggesting a critical correlation of this allele with hematologic malignancies and other pathologic conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A similar finding was also reported by others [20], though controversial results have also been published [16,21,22,25,33]. An increased frequency of the HLA-B35 allele has also been reported in some other malignancies and autoimmune diseases from different ethnic populations, including Hodgkin's lymphoma [34], autoimmune thyroiditis [35], autoimmune hepatitis [36] autoimmune arthritis [37], Moyamoya [38], and pemphigus vulgaris [39], suggesting a critical correlation of this allele with hematologic malignancies and other pathologic conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Apart of a few studies [4,16,[19][20][21][22][23][24][25][26] in which the frequency of HLA alleles has been determined in CLL patients from some ethnic populations, association of HLA alleles and CLL prognosis has not been well studied, especially in the Asian CLL patients. In a prior study we reported the frequency of some HLA class I A, B and C antigens in a limited number of CLL patients using the serological microlymphocytotoxicity technique [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations examining the frequency of the HLA system in CLL patients demonstrated inconsistent and controversial association of some HLA alleles with CLL [17][18][19]22,23]. Whereas some studies indicated no association of CLL with HLA molecules [24], others demonstrated association with a variety of HLA alleles [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…These polymorphic antigens could also influence the pathogenesis of B-cell or T-cell malignancies through continuous clonal stimulation of antigen-specific lymphocytes [16]. Many studies examined the possible association of the HLA system with lymphoproliferative disorders, but few reported HLA frequencies in CLL [17][18][19][20][21][22][23][24]. Furthermore, the frequency of HLA alleles has not been well determined in Asian CLL patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation